The future of STI screening and treatment for youth: a National Survey of youth perspectives and intentions - Vinaya Gogineni (BMC, 2021)
Abstract Background Sexually transmitted infection (STI) rates continue to rise in the U.S., with disproportionately high rates among those aged 15–24 years. Effective programs and policies are necessary to address this growing public health problem. The purpose of this study is to assess the perspectives of a national sample of youth on access to STI care and behaviors regarding STIs. Methods MyVoice, a national text message survey of youth, was used to pose four open-ended questions on STI screening and treatment to 1115 youth aged 14–24 in August 2018. A mixed-methods strategy was employed for the study. Qualitative data was analyzed using a modified grounded theory approach. Summary statistics were calculated for demographic data and prevalence of themes. Results Of the 800 participants who responded to at least one question (72% response rate), mean age was 19 years (SD = 3.1), 55% identified as female, 61% identified as non-Hispanic white, and 33% qualified for free/reduced lunch. A majority felt it would be easy to get screened (69%) or treated (68%) for an STI. Nearly all respondents (95%) stated they would share an STI diagnosis with their sexual partners. Conclusions Despite high rates of STIs among youth, most respondents reported that STI screening and treatment is accessible, and they would share an STI diagnosis with their partner.